The Impacts of Land Reclamation of Jakarta Bay on Mangrove Ecosystem - Hadi S Alikodra (Department of Forest Resources Conservation and Ecotourism - IPB University, 1996)
Significant impack resulted from the reclamation of mangrove forests, will result in its dissappearancel functional changes which in turn will affect the sea productivity of Jakarta Ray and itr other functions such as wildlife hahitat, protection against waves and winds, ahsorption of pollutants in Jakarta Bay, and sea intrusion,also the dissappearance of nature potentials to he develop as nature recreation and tourism site. Efforts should include maintenance, restoration and development of Jakarta Bay mangrove forests, especially in Muara Angke Nature Strict Reserve and the Protected Forest along the eastern part of the coast.